Innovation in materials science - Sekhar, J. A. (Key engineering materials, 2008)
""Scientific technology"" has progressively displaced ""empirical technology"" as the primary driver and basis for increasing economic development over the last four centuries. The integration of the power technologies developed during the 17th - 19th Centuries, with the mechanization of thought developed in the 20th Century, has increased the scale and efficiency of formal inventive and innovation processes as the key sources of wealth creation by innovation. In the present work, emphasis is placed on some key innovations specific to the Materials Science that has exerted such a profound.